2014
DOI: 10.1108/ssmt-09-2013-0023
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the reliability and intermetallic layer of solder joints prepared with infrared and vapour phase soldering

Abstract: Purpose – The purpose of this paper is to compare the reliability and intermetallic layer (IML) of solder joints prepared with infrared (IR) and vapour phase (VP) soldering. The reliability of 0603-sized resistors’ solder joints formed with IR and VP soldering was investigated. The IML of the joints was analysed based on image processing algorithm automatically. Design/methodology/approach – For the reliability analyses, the ageing metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 32 publications
(25 reference statements)
0
20
0
Order By: Relevance
“…Medgyes et al investigated the electrochemical migration on biodegradable materials [15], and showed that due to better wetting on different biodegradable substrates, the failure criteria may occur earlier during migration tests, compared to conventional PCBs. Our previous work focused on Cellulose Acetate (CA) and PLA materials [16][17][18]; the investigations were combined with vapour phase soldering (VPS) joining method, where quality concerning results were similar to the typical findings of VPS investigations [19][20][21][22][23] with lead-free solder alloys. Our papers also showed limiting factors of solder joint production (the biodegradable substrates have lower melting point and lower glass transition temperature than standard FR4 PCBs), and limiting mechanical parameters of the produced PCBs.…”
Section: Introductionmentioning
confidence: 83%
“…Medgyes et al investigated the electrochemical migration on biodegradable materials [15], and showed that due to better wetting on different biodegradable substrates, the failure criteria may occur earlier during migration tests, compared to conventional PCBs. Our previous work focused on Cellulose Acetate (CA) and PLA materials [16][17][18]; the investigations were combined with vapour phase soldering (VPS) joining method, where quality concerning results were similar to the typical findings of VPS investigations [19][20][21][22][23] with lead-free solder alloys. Our papers also showed limiting factors of solder joint production (the biodegradable substrates have lower melting point and lower glass transition temperature than standard FR4 PCBs), and limiting mechanical parameters of the produced PCBs.…”
Section: Introductionmentioning
confidence: 83%
“…Vapour phase soldering (VPS) is an alternative reflow soldering method to the most commonly used infra-radiation (IR) and convection reflow soldering. VPS has several advantages due to its stable soldering temperature which prevents overheating, its inert atmosphere and the reliability of the solder joints [1]. The standard VPS process is illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Many reliability issues of electronics have to be solved nowadays [1][2][3]. One of the most dangerous ones is the electrochemical migration (ECM) failure phenomenon.…”
Section: Introductionmentioning
confidence: 99%